The effect of different plasticizers on the properties of starch-protein based edible film: article / Nurul Qairawani Othman and Fariza Hamidon - Othman, Nurul Qairawani; Hamidon, Fariza (2017)
The purpose of this study is to produce edible films from starch, protein, and combination of both. Also, the aim is to investigate the effect of different types of plasticizer and their concentrations on the properties of the edible film produced as well as to compare the properties of composite edible film the one made from starch and protein. Plasticizers like glycerol, sorbitol and polyethylene glycol (PEG200) were added into formulation at various concentrations (10, 15, 20, 25 %) to increase the properties of edible films. Then the combination of starch, gelatin and plasticizers were formulated and cast on petri dish to produce composite edible films and their mechanical properties (tensile strength and elongation at break, EAB), solubility and water vapor permeability (WVP) were tested. The findings showed that, the addition of gelatin into the formulation increased the tensile strength of glycerol and sorbitol plasticized film, solubility and WVP of all types of plasticized films. Besides, the increasing concentration of plasticizers will decreased the tensile strength and solubility of glycerol and sorbitol plasticized films. The EAB of the edible films increased when the concentration of sorbitol and PEG200 increased as well as when concentration of glycerol decreased. The increasing of concentration of plasticizers did not produce significant trend on the WVP of the composite edible films. It was observed that, the edible films plasticized with glycerol has higher EAB and higher solubility when plasticized with PEG200 compared to others. However, the addition of plasticizers into the formulation does not bring significant change to the WVP of the films.